Differences in the Dental Caries Index Based on the pH Of Well Water and PDAM Water Used by Communities in Kelay District, Berau Regency - Angelia, Sheviola Wahyu Okta; Pramasari, Cristiani Nadya; Duma, Krispinus (Sean Institute, 2024)
Dental and oral diseases affect 90% of Indonesia's population, one of which is caries. Based on Basic Health Research (Riskesdas) data for the East Kalimantan region, Berau Regency has the second highest prevalence of caries or cavities after West Kutai, namely 56.08%. The environment is one of the factors that influences the occurrence of caries, one of which is water. A pH value below 6.5-8 indicates that the water is acidic, which can increase the risk factor for caries. The aim of this research is to analyse the differences in the dental caries index based on the pH of well water and PDAM water used by the community in Sido Bangen Village. This research uses observational research with a cross-sectional approach. The sample was taken using a purposive sampling technique. The population of this study was the people of Kelay District. The total sample was 78 people, who were divided into 2 groups, namely 39 research subjects who used well water and 39 research subjects who used PDAM water. The results of the independent sample T test showed that there was a difference in the DMF-T index between users of well water and PDAM water with p = 0.000 (p < 0.05). The results of the Mann-Whitney test show that there is a difference in pH values between the pH of well water and PDAM water, with p = 0.000 (p < 0.05).